The resilience of social and ecological systems: taking account of uncertainty for development - Botta, Aurélie; Bousquet, François (Perspective, 2017)
Version française de l'article The development and humanitarian community has established its own school of thought on resilience in order to link its emergency actions with its medium- and long-term development strategies. Intervention contexts are becoming increasingly uncertain and complex, raising new challenges that need to be addressed. The school of thought on social and ecological system resilience can provide complementary approaches to help understand the intervention context and the multiple dimensions of challenges, as well as to develop and assess adaptation pathways. These approaches enable accounting of ecological dynamics and interactions among social groups, provide a diversity of knowledge and potential development pathways and, ultimately, support societal transformation. Collaboration between these two schools of thought would provide valuable opportunities.